Broadening the social psychological approach to acculturation: cultural, personality and social-network approaches (Ampliación del enfoque socio-psicológico de la aculturación: perspectivas cultural, de la personalidad y de las redes sociales). Issue 3 (1st September 2020) - Benet-Martínez, Verónica; Repke, Lydia
ABSTRACT: The field of acculturation spans a rich and broad spectrum of relevant topics, types of populations and geographic areas. It has, however, been slow in incorporating theoretical insights beyond the intergroup relations perspective, neglecting contributions from other social psychology areas, such as the socio-cognitive approach, and from disciplines such as cultural and personality psychology, and the social-network perspective. The main aim of this article is to inform and broaden the understanding of micro- and meso-level acculturation mechanisms (e.g., cultural frame switching, multicultural identity structure and dynamics, intra- and inter-personal interculturality). We argue that it is time for acculturation research to apply other methodologies, rely on new theoretical paradigms and move from predicting acculturation outcomes (e.g., psychological well-being) to modelling acculturation processes. The article closes with a discussion on potential future challenges and needed directions in the social psychological study of acculturation, interculturalism and migration.